Sub-typing Daily Fatigue Progression in Chronic Fatigue Syndrome - Jason, Leonard A. (2012)
BACKGROUND: Activity logs involve patients writing down their activities and symptoms over one or more days. AIMS: The present study sought to classify daily fatigue patterns among patients with chronic fatigue syndrome (CFS) using activity logs. METHOD: Fatigue intensity was self-reported every 30 minutes in a sample of 90 patients with CFS over one day. A cluster analysis using fatigue intensity, variability, and slope was conducted. RESULTS: Three clusters emerged involving patients with different trajectories. One group evidenced high fatigue intensity, low variability, and fatigue intensity stayed the same over time. A second group had moderate fatigue intensity, high variability, and fatigue intensity decreased over time. A third group had moderate fatigue intensity, high variability, but fatigue intensity increased over time. The three clusters of patients differed on measures of actigraphy, pain, and immune functioning. CONCLUSIONS: Activity logs can provide investigators and clinicians with valuable sources of data for understanding patterns of behavior and activity among patients with CFS.